Highly Integrated Organic–Inorganic Hybrid Architectures by Noncovalent Exfoliation of Graphite and Assembly with Zinc Oxide Nanoparticles - Marcia, Mario; Vinh, Chau; Dolle, Christian; Abellan Saez, Gonzalo; Schönamsgruber, Jörg; Schunk, Torsten; Butz, Benjamin; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2016)
Liquid-phase exfoliated few-layer graphene flakes are noncovalently functionalized with tailor-made cationic water-soluble perylene diimides. By using a straightforward dip-coating approach, homogeneous ultrathin films consisting of interpenetrated nanoarchitectures can be achieved by incorporation of anionic ZnO nanoparticles. These 0D/2D assemblies pave the way for the development of novel graphene-based composite materials.
Keywords: graphene; hybrid materials; layer-by-layer assembly; nanoparticles; supramolecular chemistry